Derivación de valores económicos de la producción de leche de bovinos en la Parroquia 11 de Noviembre utilizando funciones de beneficio. - López Marcillo, Guadalupe Elizabeth (2023)
This project is carried out with the aim of making a positive contribution using veterinary clinical techniques and methods for dairy producers in the 11 de Noviembre parish of the city of Latacunga. The project seeks to derive economic values from dairy production and define criteria for genetic improvement. To achieve this, we have conducted outreach sessions with the residents, presenting the project, and we have obtained the acceptance of 10 producers with a total of 34 head of cattle. In continuation of the research work, we have established records and monitoring for each of the cows that the individuals who decide to join and be part of this project maintain.It was observed that the majority of producers have a low number of cattle, with the Holstein breed predominating at 79%, the Jersey breed at 12%, and the Brown Swiss breed at 9%. Variations in milk production were evident due to environmental and management factors, which have a significant number of deficiencies due to the lack of training among the residents in managing their lands to improve feeding and reduce expenses. The presence of mastitis and its control were also analyzed, resulting in a low incidence rate of 17%.Additionally, economic values were derived, and the production cost was calculated to be USD 0.22 per liter of milk produced. Notably, feed accounted for the main expense at USD 39.94 monthly, with an average of 358.43 liters. This yielded a cost benefit of USD 29.49 to each owner, considering that milk is sold at USD 0.35 per liter. In conclusion, the selection criteria taken into account to continue with the project are fertility, as a high degree of precocity with one calving per year is present. Furthermore, weight gain, which can be improved through proper feeding management, and lastly, the daily milk production factor is considered. Records are kept and suggestions are provided to the producers on how to surpass the current levels through the current preparation of the herd to achieve future benefits and greater productive acceptance.